INDONESIAN LANGUAGE LEARNING PROBLEMS IN THE CONTEXT OF THE INDEPENDENT CURRICULUM AT THE SENIOR HIGH SCHOOL LEVEL IN SOUTH SULAWESI - Fitriana Fitriana; Dadang S. Anshori (JURNAL NALAR PENDIDIKAN, 2024)
This research was conducted with the aim of 1)describing the problems of learning Indonesian in the context of the Merdeka curriculum at the SMA/MA level in South Sulawesi 2)describing the efforts made by teachers in overcoming the problems of learning Indonesian in the context of the Merdeka curriculum at the SMA/MA level in South Sulawesi. The type of research used is descriptive qualitative, with data collection techniques in the form of questionnaires via Google Forms. The results of this research show data that the problems of learning Indonesian in the context of the Merdeka curriculum at the SMA/MA level in South Sulawesi include: 1)teacher readiness; 2)the availability of inadequate facilities and infrastructure; 3) several teachers still do not master technology; 4)teacher creativity still needs to be improved; 5) lack of references related to training in making teaching materials; 6) misperceptions from students. Meanwhile, efforts made by teachers to overcome existing problems include: 1)attending independent curriculum seminars; 2) using an independent teaching platform; 3) joining a learning teacher community; 4) Empowering subject teacher deliberation (MGMP); 5) taking part in independent curriculum training; 6) provide students with an understanding of the concept of an independent curriculum.